2023
DOI: 10.1111/1365-2664.14474
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energies and biodiversity: Impact of ground‐mounted solar photovoltaic sites on bat activity

Abstract: Renewable energy is growing at a rapid pace globally but as yet there has been little research on the effects of ground‐mounted solar photovoltaic (PV) developments on bats, many species of which are threatened or protected. We conducted a paired study at 19 ground‐mounted solar PV developments in southwest England. We used static detectors to record bat echolocation calls from boundaries (i.e. hedgerows) and central locations (open areas) at fields with solar PV development, and simultaneously at matched sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The PLP of photovoltaic panels is indirectly demonstrated by the more and more frequent observations of the number of panel collisions and the activity of insectivorous bats [13,17,18,37] at solar farms. The main reason for this is the enhanced number of insects deceived and lured by the horizontally polarized light reflected from solar panels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PLP of photovoltaic panels is indirectly demonstrated by the more and more frequent observations of the number of panel collisions and the activity of insectivorous bats [13,17,18,37] at solar farms. The main reason for this is the enhanced number of insects deceived and lured by the horizontally polarized light reflected from solar panels.…”
Section: Discussionmentioning
confidence: 99%
“…The PLP associated with photovoltaic solar panels is of particular importance, because several studies have indicated that these panels can attract polarotactic aquatic insects to lay their eggs upon them [9,11]. Furthermore, the PLP of solar panels can be a possible indirect cause of bat-panel collisions [17,18]: the polarotactic insects attracted by the polarization of panel-reflected light can lure insectivorous bats [13], which consume these deceived insects. Photovoltaic use is expanding dramatically worldwide, and relatively little is known about their reflection-polarization characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The sustainable treatment of PV modules can reduce their toxicity to water and human beings by 10-70% compared to untreated spent panels [10]. Due to DSP being highly regarded as the next electronic waste, successful mitigation measures during PV solar panel development will serve as an option to manage climate change while supporting biodiversity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the important synthesis and review work of Smallwood (2022), effects of the installation of solar farms on habitat use by vertebrates remain poorly documented. There have been only three studies: one shows that solar farms lead to reduced bird species richness and density (Visser et al., 2019), and two show that they lead to reduced activity of several insectivorous bat species (Szabadi et al., 2023; Tinsley et al., 2023). Perturbations of insectivorous bats, which occupy high trophic levels, are likely to be linked to reductions in the abundance of their insect prey, which could be generated by reduced plant biomass in the shady conditions under solar panels (Armstrong et al., 2016; Graham et al., 2021).…”
Section: Introductionmentioning
confidence: 99%